Digital Media Utilization in Teaching Islamic Religious Education at the Elementary School Jember - Satriyo Yudho Putro; Sofyan Hadi; Suparwoto Sapto Wahono (Program Studi PGMI, 2026)
The integration of digital media has become an essential requirement in contemporary education. However, previous studies on the use of digital media in Islamic Religious Education (IRE) at the elementary school level have primarily focused on technology adoption, with limited attention to its pedagogical use in promoting interactive and student-centered learning. This condition highlights the urgency of examining not only the presence of digital media but also the depth of its implementation within the value-oriented and affective context of IRE. This study aims to explore the use of digital media in IRE learning at SD Baiturrahman Jember and to analyze the challenges faced by teachers. It employs a descriptive qualitative case study approach, with data collected through classroom observations, interviews, and documentation. The findings indicate that digital media are predominantly used for content delivery rather than interactive learning. The media used include PowerPoint, videos, images, and audio. Teachers face several challenges, such as limited digital competence, time constraints, inadequate infrastructure, and classroom management issues. this study lies in its focus on the pedagogical depth of digital media integration in IRE, highlighting the gap between technological availability and meaningful use. Practical implications include the development of interactive digital activities, strengthening teachers’ digital pedagogical competence, and providing value-based contextual training. effective integration of digital media in IRE requires not only infrastructure support but also professional development and pedagogical transformation.